Model Probing Prompting dalam Upaya Meningkatkan Hasil Belajar Matematika pada Siswa Kelas XII MA Darusslam - Nur Aisyah; Nursamsi Nursamsi; Azwan Anwar (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is a classroom action research (CAR) conducted at MA Darussalam with the aim of improving mathematics learning outcomes through the application of the Probing-Prompting model. The subjects of this study were 26 grade XII students. Data collection was carried out using learning outcome tests given before and after the application of the learning model. The collected data were analyzed quantitatively and qualitatively. The results showed that the average score of students' learning outcomes in cycle I reached 82.38, while in cycle II it increased to 86.15. Based on the learning outcome completion category used, the achievement of students' mathematics learning outcomes in cycle I was 73.07%, and in cycle II it reached 100%. The application of the Probing-Prompting model has proven effective in increasing students' motivation and understanding of the material being taught. Thus, it can be concluded that the use of the Probing-Prompting model has a positive effect on improving students' mathematics learning outcomes, showing a significant increase in their understanding and skills in solving mathematics problems.